Urokinase in Hypertensive Capsuloganglionic Hemorrhage with Intraventricular Hemorrhage: A Randomized Control Trial - Kaveeze K; S Balaji (National Board of Examinations Journal of Medical Sciences)
Background: Capsuloganglionic hemorrhage with intraventricular hemorrhage (IVH) is always associated with higher mortality and morbidity [12]. So, we did a randomized control trail in patients requiring External ventricular Drain (EVD) for hypertensive IVH with and without instilling Urokinase; to know it’s effectiveness [19]. Methods: A computerized randomized controlled trial was carried out on 30 patients who needed EVD for hypertensive capsuloganglionic hemorrhage with IVH. Patients were randomly assigned to one of two groups: test (EVD + urokinase) or control (EVD only). Graeb scores, Glasgow Outcome Scale (GOS), ICU stay, GCS, and complications were compared before and after treatment. Results: The EVD + urokinase group had better functional outcomes, a shorter ICU stay (5.8 vs. 7.8 days, p=0.044), and a much larger drop in Graeb scores (p<0.001). There was no increased risk of infection or rebleeding. Conclusion: In Hypertensive Capsuloganglionic Hemorrhage with IVH, intraventricular fibrinolysis with urokinase is a safe and effective to improve the outcome of the patient.